Technology‐enhanced writing therapy for people with aphasia: results of a quasi‐randomized waitlist controlled study. Issue 2 (10th May 2018) - Marshall, Jane; Caute, Anna; Chadd, Katie; Cruice, Madeline; Monnelly, Katie; Wilson, Stephanie; Woolf, Celia
Abstract: Background: Acquired writing impairment, or dysgraphia, is common in aphasia. It affects both handwriting and typing, and may recover less well than other aphasic symptoms. Dysgraphia is an increasing priority for intervention, particularly for those wishing to participate in online written communication. Effective dysgraphia treatment studies have been reported, but many did not target, or did not achieve, improvements in functional writing. Functional outcomes might be promoted by therapies that exploit digital technologies, such as voice recognition and word prediction software. Aims: This study evaluated the benefits of technology‐enhanced writing therapy for people with acquired dysgraphia. It aimed to explore the impact of therapy on a functional writing activity, and to examine whether treatment remediated or compensated for the writing impairment. The primary question was: Does therapy improve performance on a functional assessment of writing; and, if so, do gains occur only when writing is assisted by technology? Secondary measures examined whether therapy improved unassisted written naming, functional communication, mood and quality of life. Methods & Procedures: The study employed a quasi‐randomized waitlist controlled design. A total of 21 people with dysgraphia received 12 h of writing therapy either immediately or after a 6‐week delay. The primary outcome measure was a functional assessment of writing, which was administered in handwriting and on a computer with assistive technology enabled. Secondary measures were: The Boston Naming Test (written version), Communication Activities of Daily Living—2, Visual Analogue Mood Scales ( Sad question), and the Assessment of Living with Aphasia. Analyses of variance (ANOVA) were used to examine change on the outcome measures over two time points, between which the immediate group had received therapy but the delayed group had not. Pre‐therapy, post‐therapy and follow‐up scores on the measures were also examined for all participants. Outcomes & Results: Time × group interactions in the ANOVA analyses showed that therapy improved performance on the functional writing assessment. Further interactions with condition showed that gains occurred only when writing was assisted by technology. There were no significant interactions in the analyses of the secondary outcome measures. A treatment effect on these measures was therefore unconfirmed. Conclusions & Implications: This study showed that 21 people with dysgraphia improved on a functional writing measure following therapy using assistive technology. The results suggest that treatment compensated for, rather than remediated, the impairment, given that unassisted writing did not change. Further studies of technology‐enhanced writing therapy are warranted.